What makes a difference to patients?. (June 2013) - Johnston, Deirdre
Abstract: To make a difference to patients who increasingly suffer multiple chronic conditions, in a healthcare system that is capable of providing excellent care but is often ineffective and at cross-purposes in its application, means being prepared to take a different approach not only to the delivery of patient care, but to the education of physicians and other healthcare professionals. The model we must now practice and teach is one that emphasizes collaboration and prevention, quality and efficiency. Changes in practice recommended by the 2001 US Institute of Medicine report are being implemented system-wide, following the enactment of the US Patient Protection and Affordable Care Act. This paper discusses the evolving needs of patients with chronic psychiatric illness, and the psychiatrist's role in a rapidly changing healthcare landscape as a care provider, an interdisciplinary role model, and educator. In an aging population in which multi-morbidity is the norm, episodic, crisis-driven care is prohibitively expensive and does not serve patients well. Yet we still teach that model of care. The medications we prescribe for psychiatric illness, particularly antipsychotics, can cause and/or aggravate some of the commonest chronic medical illnesses; psychiatric educators must address the management of these complications. The management of chronic psychiatric illness in multi-morbid patients demands that we practice and teach a 'whole patient' approach to care, preferably delivered as part of a patient-centred team. The Affordable Care Act has mandated and created opportunities for new models designed to facilitate this, and a paradigm shift is needed in medical education. Clinicians must become adept at identifying underlying and contributing factors and collaborating with the patient, other providers, and the patient's family and significant others. Psychiatric formulation and patient care rely on these principles; we must now teach their application to other specialties, disciplines and professions.